O comércio mundial de armas e a exportação bélica do Brasil - Ian Cassiano Batista Cunha; Ricardo José Batista Nogueira (Revista Geonorte, 2017)
Since the end of World War II, we face a new arming race involving the great powers that are constantly struggling for economic, technological and military sovereignty. This paper’s main objective is to present some internal relations theories showing the behavior of States and their management, and to present the brazilian production capacity on war material and the destination of these products. This research is based on literature review and consultation on institutes applied in the control of war material shipments and supplies between countries database.